2017
DOI: 10.1097/ico.0000000000001209
|View full text |Cite
|
Sign up to set email alerts
|

Descemetorhexis Without Grafting for Fuchs Endothelial Dystrophy—Supplementation With Topical Ripasudil

Abstract: In Fuchs dystrophy with visual degradation due to central guttae, descemetorhexis without grafting is a viable procedure for visual rehabilitation. Careful patient selection is required, but the advent of topical ripasudil as a salvage agent suggests that a broader application of the surgery may be possible. Further study into the use of this agent is now needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
150
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(170 citation statements)
references
References 20 publications
3
150
0
3
Order By: Relevance
“…The nonresponsive patients were treated by secondary DMEK with no complications reported or by topical administration with different formulations of rho-associated protein kinase (ROCK) inhibitor, either as Y-27632 or Ripasudil (n ¼ 3). 4,39,64,93 In 1 case of severe FECD, there was a persistent paracentral edematous area of 3.5-mm diameter, but no DMEK was performed because the patient was satisfied with that outcome. 36 We observed a similar case where a patient was undergoing cataract surgery 2 weeks before DMEK.…”
Section: Planned Descemetorhexis Without Graftingmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonresponsive patients were treated by secondary DMEK with no complications reported or by topical administration with different formulations of rho-associated protein kinase (ROCK) inhibitor, either as Y-27632 or Ripasudil (n ¼ 3). 4,39,64,93 In 1 case of severe FECD, there was a persistent paracentral edematous area of 3.5-mm diameter, but no DMEK was performed because the patient was satisfied with that outcome. 36 We observed a similar case where a patient was undergoing cataract surgery 2 weeks before DMEK.…”
Section: Planned Descemetorhexis Without Graftingmentioning
confidence: 99%
“…99 In a recent study, supplementation with a ROCK inhibitor was implemented as a salvage procedure when there was no corneal resolution 2 months after Descemet stripping. 93 In the first nonresponder, Y-27632 was applied topically but was replaced by another topical formulation of Ripasudil, thereby effectively clearing the cornea within 10 days. Similarly, 2 other responders and an additional patient with a small edematous patch were administered Ripasudil, all resulting in a transparent cornea within 14 days.…”
Section: Endothelial Barrier Reformation Using Pharmacological Treatmentmentioning
confidence: 99%
“…Since then, the ability of ROCK inhibitors to encourage corneal endothelial cells to divide and attach, while reducing apoptosis, has been demonstrated . Most recently, studies using ROCK inhibitors have demonstrated that simple central Descemetorhexis without an endothelial keratoplasty in FECD can still be associated with central endothelial cell recovery to produce a clear cornea, with recovery enhanced by the use of the ROCK inhibitor ripasudil …”
mentioning
confidence: 99%
“…14 Most recently, studies using ROCK inhibitors have demonstrated that simple central Descemetorhexis without an endothelial keratoplasty in FECD can still be associated with central endothelial cell recovery to produce a clear cornea, with recovery enhanced by the use of the ROCK inhibitor ripasudil. 15 In an excellent demonstration of laboratory bench to patient bedside developments, Kinoshita et al reported a series of patients with bullous keratopathy who received injection of cultured endothelial cells after Descemetorhexis, and showed full recovery of corneal clarity. 16 Thus, the age of cellular transplantation is truly upon us.…”
mentioning
confidence: 99%
“…В последние годы появились публикации об эффективности изолированного десцеметорек-сиса (ДР) для лечения ЭДР [7,8,[11][12][13]. Показа-ния для данного способа лечения ЭДР остаются спорными.…”
unclassified